PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 3 SUNGAI LALA - Dwiana Listy Aninditha; Sri Yunita Ningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study examined the influence of the Problem Based Learning (PBL) model on eighth-grade students' mathematical communication abilities at SMP Negeri 3 Sungai Lala. A quantitative approach with a quasi-experimental design and Posttest-Only Control Design was employed. The participants consisted of two intact classes: class VIII-A served as the experimental group receiving PBL instruction, while class VIII-B functioned as the control group undergoing conventional teaching methods. Mathematical communication skills were assessed through a structured essay test. Statistical analysis revealed that students in the experimental group demonstrated significantly superior mathematical communication competencies compared to their counterparts in the control group. These findings confirm that PBL exerts a positive influence on students' capacity to communicate mathematical ideas.Keywords: Problem Based Learning, mathematical communication skills, mathematics learning